Impact of deep phenotyping: high diagnostic yield in a diverse pediatric population of 172 patients through clinical whole-genome sequencing at a single center - Akgun-Dogan, Ozlem; Tuc Bengur, Ecenur; Ay, Beril; Ozkose, Gulsah Sebnem; Kar, Emre; Bengur, Fuat Baris; Bulut, Aybike S.; Yigit, Ayca; Aydin, Eylul; Esen, Fatma Nisa; Ozdemir, Ozkan; Yesilyurt, Ahmet; et al. (Frontiers in Genetics, 2024)
Background: Pediatric patients with undiagnosed conditions, particularly those suspected of having Mendelian genetic disorders, pose a significant challenge in healthcare. This study investigates the diagnostic yield of whole-genome sequencing (WGS) in a pediatric cohort with diverse phenotypes, particularly focusing on the role of clinical expertise in interpreting WGS results. Methods: A retrospective cohort study was conducted at Acibadem University’s Maslak Hospital in Istanbul, Turkey, involving pediatric patients (0–18 years) who underwent diagnostic WGS testing. Clinical assessments, family histories, and previous laboratory and imaging studies were analyzed. Variants were classified and interpreted in conjunction with clinical findings. Results: The cohort comprised 172 pediatric patients, aged 0–5 years (62.8%). International patients (28.5%) were from 20 different countries. WGS was used as a first-tier approach in 61.6% of patients. The diagnostic yield of WGS reached 61.0%, enhanced by reclassification of variants of uncertain significance (VUS) through reverse phenotyping by an experienced clinical geneticist. Consanguinity was 18.6% of the overall cohort. Dual diagnoses were carried out for 8.5% of solved patients. Discussion: Our study particularly advocates for the selection of WGS as a first-tier testing approach in infants and children with rare diseases, who were under 5 years of age, thereby potentially shortening the duration of the diagnostic odyssey. The results also emphasize the critical role of a single clinical geneticist’s expertise in deep phenotyping and reverse phenotyping, which contributed significantly to the high diagnostic yield.